Social confrontation among students of the departments of psychological counseling and educational guidance (Journal of the College of Basic Education, 2023)
Research Abstract: The current research aimed to identify:- 1- Social confrontation among students of psychological counseling and educational guidance departments.2- Significance of differences in social confrontation according to the gender variable (male, female) among students of psychological counseling and educational guidance departments.For the purpose of achieving the objectives of the current research, the two researchers: Adopted the social confrontation scale, which consists of (30) items in its final form according to the theory of Arnold Lazarus. The statistical analysis procedures for the scale were verified by applying it to a sample of (400) male and female students. Significance of excellence for the items of the scale, as well as internal consistency and all psychometric characteristics (apparent validity and constructive validity). The scale was applied in its final form to a sample that was chosen in a random stratified manner, amounting to (260) male and female students. After applying the research tool and using appropriate statistical methods, the following results were reached: The research sample individuals have the ability to cope with the social according to the difference between the arithmetic mean and the hypothetical average, and there are statistically significant differences in the relationship to cope with the social according to the gender variable and in favor of males.Keywords: social confrontation, environmental pressures, problems